1984
DOI: 10.1007/bf02281206
|View full text |Cite
|
Sign up to set email alerts
|

Components of rational-emotive imagery: Two experiments with nonassertive students

Abstract: Unassertive students took part in two experiments to assess the contributions of emotional and cognitive rehearsal procedures in rational-emotive imagery. In each study participants received analogue treatment in groups, which met twice for one and a half hours. In Experiment 1 behavior rehearsal (BR) was more effective than emotional rehearsal (ER, which involved trying to attenuate unwanted feelings in fantasy) and cognitive rehearsal (CR, which involved examining negative, and rehearsing helpful, self-state… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

1992
1992
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 9 publications
1
4
0
Order By: Relevance
“…Similar findings are reported by other foreign authors: Thorpe, Freedman, & McGalliard, 1984;Prihozan, 2000Prihozan, , 2005 In adolescence, girls worry about relationships with peers more often than boys, and a thought that peers will appraise them negatively cause stronger anxiety for girls rather than for boys. Pasinkova (1996) found that increased anxiety (as a personality trait) caused disorganisation of cognitive activity, which is expressed in a longer information perception and processing time, deterioration of educational and intellectual achievements (Škuškovnika, 2004).…”
Section: School Anxiety Researchsupporting
confidence: 85%
“…Similar findings are reported by other foreign authors: Thorpe, Freedman, & McGalliard, 1984;Prihozan, 2000Prihozan, , 2005 In adolescence, girls worry about relationships with peers more often than boys, and a thought that peers will appraise them negatively cause stronger anxiety for girls rather than for boys. Pasinkova (1996) found that increased anxiety (as a personality trait) caused disorganisation of cognitive activity, which is expressed in a longer information perception and processing time, deterioration of educational and intellectual achievements (Škuškovnika, 2004).…”
Section: School Anxiety Researchsupporting
confidence: 85%
“…A total number of 82 studies from 84 distinct articles remained to be included in the meta‐analysis. The differences in counts were given by one article that included two different studies (Thorpe, Freedman, & McGalliard, ) and five articles that reported data on two different samples (David et al., ; Sava, Yates, Lupu, Szentagotai, & David, ; Szentagotai et al., for one sample, and Thurman, 1985a,b for the second sample). Out of these studies, 68 studies provided postintervention or follow‐up data for the comparative (between groups) analysis, and 39 provided within‐group data for pre‐post or pre‐follow‐up analysis.…”
Section: Methodsmentioning
confidence: 99%
“…A total number of 82 studies from 84 distinct articles remained to be included in the meta-analysis. The differences in counts were given by one article that included two different studies (Thorpe, Freedman, & McGalliard, 1984) and…”
Section: Selection Of Studiesmentioning
confidence: 99%
“…Reports on the same study were combined for data extraction (i.e., (a) [ 30 , 31 ], (b) [ 32 , 33 ], (c) [ 34 , 35 ] (d) [ 36 , 37 ] and (e) [ 38 , 39 ]. One report detailed two separate intervention studies and therefore, was split into ‘Study 1’ and ‘Study 2’ for data extraction [ 40 ].…”
Section: Resultsmentioning
confidence: 99%
“…In total, 162 studies fulfilled the inclusion criteria. Our review highlights that REBT interventions have been delivered across the globe, with clinical, sub-clinical and non-clinical participants across a wide variety of domains, including education and healthcare [e.g., 40 , 64 ]. The interventions were typically psychoeducational in nature, adopted the ABC framework, included homework and were delivered face-to-face in group settings by a trained practitioner.…”
Section: Discussionmentioning
confidence: 99%